Gender Differences in Medical Evaluations: Evidence from Randomly Assigned Doctors - Cabral, Marika; Dillender, Marcus (American Economic Review, 2024)
Little is known about what drives gender disparities in health care and related social insurance benefits. Using data and variation from the Texas workers’ compensation program, we study the impact of gender match between doctors and patients on medical evaluations and associated disability benefits. Compared to differences among their male patient counterparts, female patients randomly assigned a female doctor rather than a male doctor are 5.2 percent more likely to be evaluated as disabled and receive 8.6 percent more subsequent cash benefits on average. There is no analogous gender-match effect for male patients. Our estimates indicate that increasing the share of female patients evaluated by female doctors may substantially shrink gender gaps in medical evaluations and associated outcomes. (JEL H75, I11, I12, J14, J16, J28)